Immigration, job vacancies, and Beveridge Curve: Evidence from Syrian refugees in Turkey - Begen, Nazire; Mercan, Murat A.; Barlin, Hande (CAMBRIDGE UNIV PRESS, 2023)
This study investigates the impact of the massive and unexpected influx of Syrian refugees on the job vacancy rates (JVRs) and job-finding rates (JFRs) in Turkey between 2009-2015 and 2009-2018. We employed the instrumental variable approach to address potential endogeneity issues. While we found no significant causal impact of the Syrian refugees on JVR, they decreased JFR between 2009 and 2018. A reduction in JFR indicates that the Beveridge Curve shifted inwards, thereby raising matching efficiency and facilitating an improvement in labour market conditions. Furthermore, our research indicated differences in coefficients and significance in JVR and JFR across occupations, as well as different effects in these areas between the short and long term. However, the results demonstrate that the rapid and unexpected influx of Syrian refugees alleviated JVR and JFR in most of the occupation groups.
Keywords: Beveridge Curve; job vacancy rates; job-finding rates; Syrian refugees; QUASI-EXPERIMENTAL EVIDENCE; LABOR-MARKET; UNEMPLOYMENT; MIGRATION; COUNTRIES; Business & Economics